Long-term effects of land use on perinatal mortality in the Endangered Saimaa ringed seal population - Liukkonen, Lauri; Rautio, Anni; Sipilä, Tero; Niemi, Marja; Auttila, Miina; Koskela, Jouni; Kunnasranta, Mervi (Endangered Species Research)
Human disturbance can affect the viability of wildlife populations partly through its effects on breeding success. Land use as a form of disturbance may do so by fragmenting the key environments of certain species. We used statistical pattern recognition methods to estimate the long-term effects of human disturbance on the Endangered, landlocked population of the Saimaa ringed seal Pusa hispida saimensis by examining how various densities of buildings on lake shores have altered the survival of juveniles and the persistence of the population. In addition, we examined whether disturbance caused by different intensities of land use would further reduce the long-term persistence of the population. We also provide estimates of the quality of Lake Saimaa shorelines as breeding habitat in relation to building density. Our results show that at present, the lairs of Saimaa ringed seals are located closer to potential sources of human disturbance than they were in the past and that land use intensity has an effect on juvenile mortality. Perinatal mortality increases significantly in more densely developed areas, where the nearest building is within 800 m of a birth lair. In addition, 29% of the shoreline of Lake Saimaa is no longer suitable for ringed seals due to intensive land use. Our results illustrate how human disturbances can significantly compromise juvenile survival and therefore the long-term existence of this Endangered population. 2017